Growth of Chlorella vulgaris in High Concentrations of Nitrate and Nitrite for Wastewater Treatment - Taziki, Mahboobeh; Ahmadzadeh, Hossein; Murry, Marcia A. (Current Biotechnology, 2015)
Background: Contamination of groundwater with nitrate has become an important environmental issue. Microalgae are especially effective agents for the removal of nitrate and nitrite from wastewaters, leading to a variety of bioremediation scenarios where algae assimilate nitrogen and convert it to biomass thus reclaiming contaminated water. This study evaluates the effects of high nitrate and nitrite concentrations on the kinetics of cell growth and nitrogen removal by Chlorella vulgaris. Methods: Algal growth and nitrate removal from media containing initial nitrate concentrations ranging from 1094 to 3000 mg L-1 were monitored in batch growth. Nitrite as the sole N source and simultaneous removal of nitrate and nitrite was also investigated. Results: Maximum growth and nitrate removal rates were 3.6 g L-1 and 16.4 mg L-1 h-1 respectively at a nitrate concentration of 2400 mg L-1 while 3000 mg L-1 nitrate appeared to inhibit growth yield but not nitrate uptake. Nitrite as the sole N source (400 mg L-1) resulted in optimal growth of Chlorella vulgaris with a maximum biomass of 3.16 g L-1. Nitrate and nitrite concentrations of 800 and 150 mg L-1 produced maximum growth rate and biomass production of 7.8 g L-1 biomass. Conclusion: This study demonstrate the potential of Chlorella vulgaris to efficiently remove and utilize both nitrate and nitrite from culture medium even at high initial concentrations while achieving high biomass productivity.
Keywords: Nitrate